New remains of Nothrotheriinae (Mammalia, Xenarthra) from Late Pleistocene fluvial deposits of Northern Pampa (Santa Fe Province, Argentina). (January 2019) - Vezzosi, Raúl I.; Brandoni, Diego; Brunetto, Ernesto; Zalazar, María Cecilia
Abstract: In this contribution the record of a Nothrotheriinae (Xenarthra, Tardigrada) ground sloth is reported from the Late Pleistocene of the Northern Pampa of Santa Fe Province, Argentina. The stratigraphic unit where the fossil was collected corresponds to fluvial-palustrine sediments of the Timbúes Formation, outcropping along the Carcarañá River valley. The relative stratigraphic position of this lithostratigraphic unit, observed in several sections mainly on the Paraná River cliffs near Carcarañá River distal area, suggests that it was deposited during the Last Interglacial Stage. The specimen (MPAHND-135), assigned to Nothrotherium cf. torresi, is represented by the proximal two-thirds of a left femur that shows a prominent lesser trochanter and no connection between the third trochanter and the ectepicondyle. The presence of Nothrotherium cf. torresi in sediments related to humid conditions supports the idea that Nothrotheriinae had great ecological tolerance and was capable of inhabiting climates ranging from cold and arid, as was previously proposed, to warm and humid. Highlights: Fossil of Nothrotheriinae from fluvial deposits of Late Pleistocene of Argentina is presented. The stratigraphic sequence supports the existence of humid conditions in the Northern Pampa. This record supports the idea that Nothrotheriinae was capable of inhabiting climates ranging from cold–arid to warm–humid. Six taxa of Nothrotheriinae were recorded from the Late Pleistocene of Santa Fe Province, Argentina.